Mosaic Brain Aneuploidy in Mental Illnesses: An Association of Low-level post-zygotic Aneuploidy with Schizophrenia and Comorbid Psychiatric Disorders - Yurov, Yuri B.; Vorsanova, Svetlana G.; Demidova, Irina A.; Kolotii, Alexei D.; Soloviev, Ilia V.; Iourov, Ivan Y. (Current Genomics, 2018)
Background: Postzygotic chromosomal variation in neuronal cells is hypothesized to make a substantial contribution to the etiology and pathogenesis of neuropsychiatric disorders. However, the role of somatic genome instability and mosaic genome variations in common mental illnesses is a matter of conjecture. Materials and Methods: To estimate the pathogenic burden of somatic chromosomal mutations, we determined the frequency of mosaic aneuploidy in autopsy brain tissues of subjects with schizophrenia and other psychiatric disorders (intellectual disability comorbid with autism spectrum disorders). Recently, post-mortem brain tissues of subjects with schizophrenia, intellectual disability and unaffected controls were analyzed by Interphase Multicolor FISH (MFISH), Quantitative Fluorescent in situ Hybridization (QFISH) specially designed to register rare mosaic chromosomal mutations such as lowlevel aneuploidy (whole chromosome mosaic deletion/duplication). The low-level mosaic aneuploidy in the diseased brain demonstrated significant 2-3-fold frequency increase in schizophrenia (p=0.0028) and 4-fold increase in intellectual disability comorbid with autism (p=0.0037) compared to unaffected controls. Strong associations of low-level autosomal/sex chromosome aneuploidy (p=0.001, OR=19.0) and sex chromosome-specific mosaic aneuploidy (p=0.006, OR=9.6) with schizophrenia were revealed. Conclusion: Reviewing these data and literature supports the hypothesis suggesting that an association of low-level mosaic aneuploidy with common and, probably, overlapping psychiatric disorders does exist. Accordingly, we propose a pathway for common neuropsychiatric disorders involving increased burden of rare de novo somatic chromosomal mutations manifesting as low-level mosaic aneuploidy mediating local and general brain dysfunction.
Keywords: Somatic genome variations